Diet Quality and Mortality, Stunting and Wasting in Children Aged 6–59 Months: An Ecological Analysis from the Global Dietary Database. (29th May 2020) - Miller, Victoria; Webb, Patrick; Cudhea, Frederick; Zhang, Jianyi; Shi, Peilin; Reedy, Julia; Puklin, Leah; Micha, Renata; Coates, Jennifer; Mozaffarian, Dariush
Abstract: Objectives: Empirical evidence on the relationship between diet quality metrics and child growth outcomes is sparse. We investigated the associations between the Infant and Young Child Minimum Dietary Diversity (IYCMDD) and Dietary Approaches to Stop Hypertension (DASH) scores, and under-5 mortality and disability-adjusted life years (DALYs) due to stunting, wasting, underweight and overweight/obesity in children aged 6–59 months. Methods: The Global Dietary Database (GDD) uses Bayesian hierarchical modeling methods to combine individual-level dietary intake from national and sub-nationally representative surveys with other country-level data to estimate mean national intakes for 55 dietary factors. Dietary data for children from 185 countries was obtained from the GDD. Data on under-5 mortality rates and disease specific DALYs were obtained from the World Bank's World Development Indicators and the Global Burden of Diseases study, respectively. We assessed country- and sex-stratum level cross-sectional associations between the IYCMDD and DASH scores, and mortality and DALYs using Poisson regression models, adjusting for individual and national-level confounders (sex, education, urbanicity, unemployment rate, poverty rate, income, and geographic region). Results: In 2015, a higher IYCMDD score was associated with a lower risk of under-5 mortality (odds ratio [OR] 0.88, 95% CI 0.86–0.90, P -value < 0.001 for a 1-unit increase) and DALYs linked to stunting (0.67, 0.67–0.68, P -value < 0.001), wasting (0.70, 0.69–0.70, P -value < 0.001), and underweight (0.70, 0.70–0.71, P -value < 0.001). No significant association with overweight/obesity (0.99, 0.97–1.01, P -value = 0.479) was observed. A higher DASH score was associated with a decreased risk of DALYs linked to under-5 mortality (0.94, 95% 0.93–0.95, P -value < 0.001), stunting (0.87, 0.87–0.88, P -value < 0.001), wasting (0.89, 0.88–0.89, P -value < 0.001), and underweight (0.88, 0.87–0.89, P -value < 0.001), and an increased risk of overweight/obesity (1.02, 1.01–1.02, P -value < 0.01). Conclusions: Higher IYCMDD and DASH scores were protective against the risk of death and stunting and wasting in children, but not overweight/obesity. Our findings suggest a need to prioritize appropriate metrics relevant to the double burden of malnutrition. Funding Sources: Gates Foundation.